Isotone cones in Banach spaces and applications to best approximations of operators without continuity conditions. (4th May 2018) - Li, Jinlu
Abstract: In this paper, we introduce the concept of isotone cones in Banach spaces. Then, we apply the order monotonic property of the metric projection operator to prove the existence of best approximations for some operators without continuity conditions in partially ordered Banach spaces.